2005
DOI: 10.1111/j.1365-2036.2005.02619.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in adult coeliac disease

Abstract: Summary Background : Fatigue is reported by many adults at the moment of diagnosis of coeliac disease and during follow‐up. Aim : To evaluate the prevalence, characteristics and associations of fatigue in adult coeliac disease patients. Methods : The investigated sample comprised adults from Campania, Italy. A total of 130 coeliac disease patients were consecutively recruited in both treated (59 on gluten‐free diet) and untreated conditions (71 on normal diet). The control group was made up of 80 healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
3
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 21 publications
5
79
3
2
Order By: Relevance
“…The mainstay of treatment for CD is strict life-long adherence to a gluten-free diet (GFD). For most patients, this results in full clinical and histological remission (Holmes & Catassi, 2000) and is associated with improvements in symptoms and quality of life (Midhagan & Hallert, 2003), a decrease in long term health risks and health gains for problems associated with CD such as infertility, fatigue (Siniscalchi et al, 2005), and depression (Hallert & Sedvall, 1983;Hallert et al, 2002;Whitaker, West, Holmes and Logan, 2009). The GFD is restrictive and can be difficult for some patients to follow however and the most common cause of persistent symptoms is gluten consumption (Dewar et al, 2012;Hopper, Hadijvassiliou, Butt & Sanders, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The mainstay of treatment for CD is strict life-long adherence to a gluten-free diet (GFD). For most patients, this results in full clinical and histological remission (Holmes & Catassi, 2000) and is associated with improvements in symptoms and quality of life (Midhagan & Hallert, 2003), a decrease in long term health risks and health gains for problems associated with CD such as infertility, fatigue (Siniscalchi et al, 2005), and depression (Hallert & Sedvall, 1983;Hallert et al, 2002;Whitaker, West, Holmes and Logan, 2009). The GFD is restrictive and can be difficult for some patients to follow however and the most common cause of persistent symptoms is gluten consumption (Dewar et al, 2012;Hopper, Hadijvassiliou, Butt & Sanders, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Using the modified Self-Rating Depression Scale, Addolorato et al 51 described persistent depression after one year of GFD in celiac patients, Zingone et al 57 and Siniscalchi et al 58 showed that depression was present in CD at diagnosis, but that it persisted or even worsened in patients on a GFD. Nachman et al, 44 using the Beck Depression Inventory, showed that depressive symptoms were highly prevalent in untreated CD and there was a significant improvement in psychological symptoms after one year and four years of GFD.…”
Section: Depressionmentioning
confidence: 99%
“…In the last decade a small number of studies have more directly addressed these issues. Siniscalchi et al in 2005 demonstrated that celiac patients both at diagnosis and when on a GFD had higher levels of fatigue than healthy controls using a variety of validated scales. 58 Perhaps more surprisingly, fatigue was not significantly different between newly diagnosed celiac patients and those on an established GFD.…”
Section: Fatiguementioning
confidence: 99%
See 2 more Smart Citations